2017
DOI: 10.1542/peds.2016-2964
|View full text |Cite
|
Sign up to set email alerts
|

Early Hearing Detection and Vocabulary of Children With Hearing Loss

Abstract: BACKGROUND AND OBJECTIVES To date, no studies have examined vocabulary outcomes of children meeting all 3 components of the Early Hearing Detection and Intervention (EHDI) guidelines (hearing screening by 1 month, diagnosis of hearing loss by 3 months, and intervention by 6 months of age). The primary purpose of the current study was to examine the impact of the current EHDI 1-3-6 policy on vocabulary outcomes across a wide geographic area. A secondary goal was to confirm the impact of other demographic variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
142
2
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(172 citation statements)
references
References 26 publications
17
142
2
11
Order By: Relevance
“…First, the possible presence of selection bias (health care access bias) could not be excluded completely, because our study is a retrospective study from a single facility with a relatively small sample size. In terms of SNHL severity, M‐M SNHL vs M–P SNHL were 57% vs 43% in a prior cross‐section study (Yoshinaga‐Itano et al, 2017) and 60% vs 40% in the current study, suggesting that our cohort may be representative of patients with SNHL in other institutions and that our findings might be generalizable to other SNHL patients.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…First, the possible presence of selection bias (health care access bias) could not be excluded completely, because our study is a retrospective study from a single facility with a relatively small sample size. In terms of SNHL severity, M‐M SNHL vs M–P SNHL were 57% vs 43% in a prior cross‐section study (Yoshinaga‐Itano et al, 2017) and 60% vs 40% in the current study, suggesting that our cohort may be representative of patients with SNHL in other institutions and that our findings might be generalizable to other SNHL patients.…”
Section: Discussionsupporting
confidence: 57%
“…Despite advances in screening and cochlear implantation (Monshizadeh et al, 2018), there are still many children with hearing loss that suffer from speech and language problems for a variety of reasons, including delayed diagnosis/intervention, failed follow‐up, sporadic attendance of auditory‐verbal therapy, and decision not to use hearing aids (Lü et al, 2011; Fitzpatrick et al, 2017). Additionally, even after intervention with hearing amplification and cochlear implants, SNHL places children at risk for language delay (Tomblin et al, 2015; Yoshinaga‐Itano et al, 2017), executive functioning deficits (Kronenberger et al, 2014), and visual cognitive impairment (Dye and Hauser, 2014; Turgeon et al, 2012), leading to life‐long consequences for affected children.…”
Section: Introductionmentioning
confidence: 99%
“…Research with D/HH persons found that social participation and feeling included in group conversations as well as being recognized and accepted as a deaf member in their environment were related to QoL (Kushalnagar et al, ). Research has also shown that having a deaf parent is associated with benefit to a deaf child (Hall, Smith, Sutter, DeWindt & Dye, ; Yoshinaga‐Itano, Sedey, Wiggin & Chung, ). Deaf mentor programs provide an alternative way to connect a family, comprised of hearing parents with a D/HH child, with a D/HH adult role model.…”
Section: Discussionmentioning
confidence: 99%
“…Det er internasjonal enighet om at tidlig diagnostisering og oppfølging av hørselstap er viktig for at barna skal ha en god språkutvikling (13,14). Andre faktorer som er vist å ha en positiv innvirkning på språkutviklingen, er blant annet høyt utdanningsnivå hos mor og at barnet ikke har tilleggsvansker (14). En stor andel av barna har imidlertid dårlig språkutvikling uten at man har funnet årsaken til det.…”
Section: Cerebral Mr Og Hørselstapunclassified